Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaan: Studi pada Bank Konvensional yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2020-2024 - Ariefani Tri Kurniati; Muhamad Syaichu (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to analyse the effects of profitability, firm growth, dividend policy, Loan-to-Deposit Ratio (LDR), and institutional ownership on firm value in conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Firm value is proxied by Price to Book Value (PBV). This research uses a quantitative approach, drawing on secondary data from companies' annual financial reports and Bloomberg. The sample was selected using purposive sampling, yielding 14 conventional banks and a total of 64 observations over five years. Data analysis was performed using multiple linear regression in SPSS. The results show that profitability and dividend policy have a positive and significant effect on firm value. Meanwhile, firm growth does not have a significant effect on firm value. Conversely, the Loan-to-Deposit Ratio (LDR) and institutional ownership have a negative and significant effect on firm value. These findings indicate that investors appreciate banks with strong earnings performance and consistent dividend distributions. Conversely, a high LDR and excessive institutional ownership tend to be perceived as increased risk, potentially decreasing firm value. This study has implications for bank management to optimise financial performance and maintain a balanced risk profile, and for investors to be more discerning in assessing companies' prospects.